Penamaan Diri Masyarakat Bima Sebagai Sapaan Hormat Kepada Orang yang Dituakan: Kajian Fonologis dan Kontribusinya dengan Pengajaran di SMP - Mutlak Mutlak; Arifuddin Arifuddin; Kamaluddin Yusra (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The study addresses honorific greeting delivered by Bima community using Donggo dialect to greet others. Specifically, the honorific address is used to greet elders using specific names that the local culturally indicates high respocet and honor. This study used qualitative approach and rooted on the sociolinguistics as the foundation of the understanding of the socio-cultural perspectives. The site of the study was Mbawa village, Donggo ditrict, Bima Regency. A number of local community consisting of 50 adult men and 50 adult women were observed as the informants of the study. Data were collected using direct observation and interview. Results show that Bima community perceive greeting is socially embedded in the culture to raise honor to others, elders, mates and the younger. The culture system in the Bima tradition is using modified self-naming to put respect and honor. The system of honorific address socially expresses politeness and religious values that root from the Islamic teaching. As the address system embeds cultural values that in sociolinguistic refers to politeness this study adversely contributes teaching language for secondary school students, implying that self-naming to express honorific address is contributable to school curriculum.